Efektivitas Metode Mind Mapping dalam Meningkatkan Hasil Belajar Fikih Materi Zakat Fitrah - Maemunah Maemunah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research is a Classroom Action Research (CAR) conducted at MI Darussalam Barang, X District, Y Regency, with the aim of improving student learning outcomes in Fiqh subjects, especially in Zakat Fitrah material, through the application of the Mind Mapping learning method. This research was conducted in two cycles, where each cycle consisted of two meetings that went through four stages: planning, action, observation, and reflection. This research was conducted because it was found that there were still students who had not achieved the Minimum Completion Criteria (KKM), caused by the lack of student involvement in learning, as well as the use of methods that were less effective and varied, resulting in a lack of enthusiasm for learning and boredom in students. The formulation of the problem in this study is: 1) How is the application of the Mind Mapping learning method to improve learning outcomes in the Fiqh subject of Zakat Fitrah in class IV MI Darussalam Barang? 2) How is the improvement in learning outcomes in the Fiqh subject of Zakat Fitrah after the application of the Mind Mapping method in class IV MI Darussalam Barang?The results of the study showed an increase in student learning outcomes on the subject of Zakat Fitrah after the Mind Mapping method was applied, which can be seen from the level of student learning completion in each cycle. In the pre-cycle, student completion was 46% with an average learning outcome of 70.36. In cycle I, completion increased to 82% with an average learning outcome of 81.61. In cycle II, completion reached 93% with an average learning outcome of 88.66, indicating a significant increase in student learning outcomes.